Analisis Transmisi Harga Bawang Merah Di Provinsi Sumatera Utara - Sembiring, Yanita Melissa Br; Rahmanta; Iskandarini (Universitas Medan Area, 2024)
Shallot are vegetables that often experience problems in the off-farm aspect, namely high price fluctuations because shallots are a commodity that can cause inflation. This study aims to analyze the transmission pattern of shallot prices at the producer, wholesaler, and consumer levels and to analyze the factors that influence the formation of shallot price at the consumer level in North Sumatra Province. The data studied is monthly data for 2016-2020, totaling 60 observations. The analytical model used in this research is the Asymmetric Error Correction Model (AECM). The results showed that price transmission between shallot marketing agencies in North Sumatra Province was asymmetric in the short and long term in the relationship between wholesalers-producers and consumers-producers. Asymmetric price transmission in the short term is formed due to adjustment costs in line with price changes that occur. Meanwhile, long-term price transmission occurs as a result of the abuse of market power by buyers